Perubahan Paradigma Pelaksanaan Tutorial untuk Mata Kuliah Pemantapan Kemampuan Mengajar pada Masa Pandemi Covid-19 - Dewi Wardah Mazidatur Rohmah; Muhammad Dhika Arif Rizqon (Journal on Education, 2024)
This study explores the differences in the implementation of tutorials of Teaching Practice Course or known as Pemantapan Kemampuan Mengajar (PKM) in Universitas Terbuka before and during the Covid-19 pandemic. This study specifically also aims to investigate the perceptions of tutors and students regarding these changes. The research method used was qualitative with two tutors and 20 students participating as research subjects. The results show differences in teaching approaches, media used, and assignments given in PKM during and before pandemic. During pandemic, tutors face challenges in measuring students’ achievements and in accommodating variations in the application of affective factors in PKM class. Meanwhile, students experience confusion in online learning, although they acknowledge some advantages such as cost savings and opportunities for collaborative practice. In conclusion, ongoing adaptation is necessary to ensure optimal learning quality in pandemic situations. Keywords: Covid-19 pandemic, PKM, UT Tutorial, Tutor’s Perception, Student’s Perception